Mass-transfer in close binary and their companions. Issue 7 (July 2016) - Liao, Wenping; Qian, Shengbang; Zhu, Liying; Li, Linjia
Abstract: Secular and/or cyclical orbital period variations of close binaries can be derived by analyzing the (O-C) diagram. The secular variations are usually explained as mass transfer between components, while the most plausible explanation of the cyclic period changes is the light-travel time effect (LTTE) through the presence of a third body. Mass transfer and additional companions in close binary systems are important for understanding the formation and evolution of the systems. Here, UV light curves of several close binaries based on the Lunar-based Ultraviolet Telescope (LUT) observations are presented and analyzed with the Wilson-Devinney (W-D) method. Then, based on those light-curve solutions and new analysis of the orbital period variations, the multiplicity, geometrical structure and evolution state of targets are discussed.